USIA DAN TINGKAT EOSINOFIL PASIEN BRONKO PNEUMONIA PADA BALITA DI RS ISLAM SURABAYA - Pramono, Bony; Irawan, Dany; Sukmawardani, Maretha; Rizqi, Nuris Umi; Khamida, Khamida (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2019)
Pneumonia is any state of inflamation where some oral of the alveoliare filled with fluid and blood cells.The total of pneumonia in children at year2013 is 15%, is still quite high. In bacterial infections such as pneumonia,usually indicates with increasing number of leukocytes (leukocytosis). Some studies, inverse correlation it with an age. Leukocytosis consists of several types, such as eosinophilia. Significant eosinophilia can occur in newborns and it will decrease constantly at old. Other study said that eosinophilia occur due to several conditions,one of them due to infection and response to foreign antigens. This research used descriptive correlational and crosssectional research method. Materials data sources obtained from patients medical records from 2014 to 2016 with bronchopneumonia at Jemur sari Surabaya Islamic Hospital. This study used chi-square analysis with interpretation p-value 0,05 with SPSS  version 21. The results  obtained 11 patients with eosinophilia, 3 of patients (27,3%) aged 0-12 months, and 8 patients (72,7%) aged 13-59 months. Then in 76 patients with noeosinophilia or normal eosinophiliaor 21 patients (27,6%) aged 0-12 months, and 55 patients (72,4%) aged 13-59 months. The result bivariate analysis of correlation age with eosinophil level of bronchopneumonia patient showed no significant relationship (p-value 0.05). The conclusion of this research there was no signigficant relationship between age and eosinophil level  in bronchopneumonia  patients aged 0-59 months. Therefore, age can not be an indicator to eosinophils levels during inflamation procesess or other needed indicators that support diagnosis. Keywords: Age, eosinophils, bronchopneumonia